Novel low-cost composite-structure high-entropy ceramic coating as well as preparation method and application thereof
Through the adjustment of the middle layer structure and process parameters of the design layer, a new low-cost composite structure high-entropy ceramic coating with excellent high-temperature mechanical properties and oxidation resistance was prepared, which solved the problem of low hardness and poor wear resistance at high temperatures. Problem, extending the service life of the tool.
Patent Information
- Application Number
- CN202411277276.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing tool coatings have low hardness at high temperatures, weak wear resistance and weak crack resistance, resulting in excessive thermal load on the edge and short service life.
Using the preparation method of a new low-cost composite structure high-entropy ceramic coating, the design layer mid-layer structure (support layer, transition layer and functional layer) and process parameters adjustment, including the synchronous deposition of TiZrAlCrSiN and TiZrAlCrSiMN targets, forming high-temperature mechanical properties and coating with antioxidant properties.
It improves the high-temperature hardness, wear resistance and oxidation resistance of the coating, reduces the thermal load of the tool edge, extends the cutting life of the tool, and enhances the overall performance of the coating through structural regulation.
Smart Images

Figure CN119121140A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of tool coatings, and in particular to a novel low-cost composite structure high-entropy ceramic coating and a preparation method and application thereof. Background Art
[0002] Using physical vapor deposition technology (PVD) to coat the tool surface with high hardness, low friction, anti-oxidation, and wear-resistant coating materials can provide good protection for cutting tools and extend the service life of tools. Currently, the commonly used tool coating materials are mainly transition metal nitrides. In recent years, with the continuous improvement of industrial technology, the comprehensive performance and preparation of hard coatings, such as hardness, wear resistance, oxidation resistance, erosion resistance, corrosion resistance, crack resistance, and bonding strength with the substrate, have been put forward higher and higher requirements. The results of these improvements depend on the multi-element, multi-structure, nano-, and gradient composite composition of the hard coating.
[0003] At present, how to improve the preparation process of existing coatings and obtain a high-performance (high-temperature hardness, wear resistance, crack resistance, etc.) composite structure high-entropy ceramic coating through low-cost preparation technology is a technical problem that needs to be solved urgently in this field.
[0004] In the Chinese patent with application number 202310681051.4, a bonding layer with good toughness and low hardness is set between the tool substrate and the multi-layer coating to improve the bonding strength of the coating. However, the transition layer is single, the composition difference between the bonding layer and the periodic composite layer is large, there is a difference in thermal expansion coefficient, and the coating is prone to cracking during use and fails prematurely; the thickness of the bonding layer is too thin, although it can improve the bonding strength, it cannot provide a good support for the composite alternating layer and the functional layer, which can easily cause the coating to fail early. The hardness of the coating after high-temperature annealing is a major mechanical parameter of the thermal stability of the coating structure, and it is also an important indicator of whether it can be used for a long time. The Al-based coating of this invention has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and it is easy to wear during tool cutting. In the Chinese patent with application number 201680023831.8, the hardness of the embodiment is shown as 2200HV-3200HVG, which is low and the wear resistance needs to be improved; the purpose of the invention is to improve the anti-adhesion performance during the cutting of titanium alloys; the coating composition of the invention is mainly Al element, and it has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and the tool is prone to wear during cutting; the embodiment shows that the coating thickness is about 3um, the coating thickness is relatively thin, and the impact resistance needs to be improved; in the coating preparation process, the coating is directly plated after Ar ion etching, and the bonding strength needs to be improved in order to design the hardness gradient result. In the Chinese patent with application number 202310559774.7, magnetron sputtering is used. It can be seen from the attached drawings of the embodiments that the bonding strength (Lc1) between the coating and the substrate is weak, and the embodiment before oxidation is less than 5N, and the crack resistance is weak; the hardness of the embodiment is only 28.8GPa, and the wear resistance needs to be improved; the coating thickness is thin, and the embodiment shows only about 1um, and the impact resistance is not strong; during the coating preparation process, 3 groups of target materials are sputtered at the same time, the process is complicated, the repetition rate is low, and the cost is high. The task of the hard coating is not only to provide wear protection for the cutting tool substrate, but more importantly, to provide thermal protection for the substrate. Therefore, in the three Chinese patents, the common defects include that during continuous cutting, the tool-chip and tool-workpiece contact areas usually reach higher temperatures. The thick coating with low thermal conductivity perpendicular to the tool surface and parallel to the tool surface can provide a thermal barrier for the tool substrate, allowing the generated heat to be transferred to the chips, thereby reducing the thermal load of the tool edge and preventing or delaying the plastic deformation of the tool edge. This point was not taken into account during the above coating preparation process. Summary of the invention
[0005] The present invention designs and develops a new type of low-cost composite structure high-entropy ceramic coating. The purpose of the invention is to solve the problems of excessive thermal load on the cutting edge during the use of existing tools, low high-temperature hardness of the coating, weak wear resistance, and weak crack resistance.
[0006] The present invention designs and develops a novel method for preparing a low-cost composite structure high-entropy ceramic coating. The purpose of the present invention is to provide a method for preparing a novel low-cost composite structure high-entropy ceramic coating with a layer-in-layer structure ("sandwich" structure) through coating structure design and process parameter adjustment during the preparation process.
[0007] The present invention designs and develops a novel low-cost composite structure high entropy ceramic coating application, and the invention aims to solve the application problem of dry cutting tool coating.
[0008] The technical solution provided by the present invention is:
[0009] A novel method for preparing a low-cost composite structure high-entropy ceramic coating comprises the following steps:
[0010] Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, heat the substrate, and perform ion implantation;
[0011] Step 2: Adjust the flow rate of nitrogen and argon, maintain the vacuum state, and turn on the TiZrAlCrSi target arc power supply to deposit the support layer; wherein the nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and the argon partial pressure decreases from 2.4-3.6Pa to 0;
[0012] Step 3: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiM target arc power supply to deposit the transition layer, and then turn off the TiZrAlCrSi target arc source power supply and the TiZrAlCrSiM target arc source power supply;
[0013] Step 4: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiM target arc power supply to deposit the functional layer, then turn off the TiZrAlCrSiM target arc power supply and cool it to obtain the novel low-cost composite structure high-entropy ceramic coating.
[0014] Preferably, in step 1, the cleaning process of the sample to be plated comprises: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface; and
[0015] Evacuate to 5×10-2Pa, heat to 400-500℃ and keep warm for 60min.
[0016] Preferably, in step 1, the ion implantation conditions include: selecting Ti as the cathode, an extraction voltage of 10-15 kV, a trigger frequency of 0-15 Hz, controlling the target current to 80-12 mA, and an implantation time of 30 min.
[0017] Preferably, in step 2, the coating rotation speed is set to 2-4 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
[0018] Preferably, in step three, the coating rotation speed is set to 1-2 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
[0019] Preferably, in step 4, the coating rotation speed is set to 1-2 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
[0020] Preferably, the TiZrAlCrSiM target is Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.05≤d≤0.10, 0.03≤e≤0.05, 0.02≤f≤0.05, a+b+c+d+e+f=1, current is 90~120A, bias voltage is -50~-350V, and deposition time is 10~30min;
[0021] Set the TiZrAlCrSi target to Ti p Zr q Al r Cr s Si t , where p, q, r, s, t satisfy 0.40≤p≤0.55, 0.25≤q≤0.30, 0.10≤r≤0.25, s=0.05, t=0.05, p+q+r+s+t=1, current is 90~120A, bias voltage is -50~-350V, deposition time is 10~30min;
[0022] Among them, 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.05, 0≤|te|≤0.10.
[0023] A novel low-cost composite structure high-entropy ceramic coating is prepared using the novel low-cost composite structure high-entropy ceramic coating preparation method, wherein the novel low-cost composite structure high-entropy ceramic coating comprises a support layer, a transition layer and a functional layer deposited in sequence;
[0024] Wherein, the support layer comprises a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited sequentially, the transition layer comprises a TiZrAlCrSiN layer and a TiZrAlCrSiMN layer deposited periodically and alternately, and the functional layer comprises a TiZrAlCrSiMN layer;
[0025] The chemical composition and mass percentage of the TiZrAlCrSi layer are as follows: Ti: 40% to 55%, Zr: 25% to 30%, Al: 10% to 25%, Cr: 5%, Si: 5%;
[0026] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 15%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0027] The chemical composition and mass percentage of the TiZrAlCrSiMN layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 12.5%, Cr: 2.5% to 5%, Si: 1.5% to 2.5%, M: 1% to 2.5%, N: 50%; M represents one or more of Hf, Y, and Nb.
[0028] Preferably, the thickness of the support layer is 0.5-1.5 um, the thickness of the transition layer is 4.5-7.5 um, and the thickness of the functional layer is 0.5-1.5 um.
[0029] A novel low-cost composite structure high-entropy ceramic coating is applied in a dry cutting tool, and the novel low-cost composite structure high-entropy ceramic coating is used.
[0030] The beneficial effects of the present invention are:
[0031] 1. In the composition of the novel low-cost composite high-entropy ceramic coating provided by the present invention, the TiZr-based coating, the Zr element at high temperature directly promotes the formation of thermodynamically stable rutile TiO2, and further leads to the formation of a dense TiO2-based structure (when Zr replaces Ti in TiO2 to form (Ti, Zr) O2), increasing the high-temperature mechanical properties of the coating (high-temperature hardness and high-temperature wear resistance); the introduction of small-radius Si elements, in the coating, the Si element mainly exists in the form of Si3N4 amorphous, making the coating gradually dense and increasing the hardness of the coating; Al and Cr will generate Al2O3 and Cr2O3 protective oxide layers during the oxidation process, which can effectively prevent further diffusion of oxygen into the cemented carbide and ensure the high oxidation resistance of the coating. Adding Hf, Y, and Nb elements can produce solid solution strengthening to improve the strength and hardness of the coating. The prepared coating has a high mixing entropy and tends to form a simple solid solution or an amorphous structure, which can meet the strengthening requirements of high-entropy alloys; the melting point of high-entropy alloys is not a fixed value, but is affected by multiple factors such as composition and crystal structure. This is related to its high entropy effect and hysteresis diffusion effect. The atomic diffusion rate of high entropy alloys is lower than that of general traditional alloys at high temperatures, which hinders the sliding of grain boundaries in the alloys under high temperature environments, but still maintains high high-temperature strength. Therefore, high entropy alloys containing high-melting-point elements have a relatively high overall melting point, which can improve the high-temperature stability of high-entropy alloy nitride ceramic coatings.
[0032] 2. The new low-cost composite high-entropy ceramic coating structure provided by the present invention includes a support layer columnar crystal (composition changes, transition from metal to nitride) + a transition layer nano multilayer structure + a functional layer columnar crystal structure. This structural coating can provide a good thermal barrier for the tool substrate. The coating material has a low thermal conductivity perpendicular to the tool surface and a high thermal conductivity parallel to the tool surface, which maximizes the transfer of generated heat to the chips, thereby reducing the thermal load on the tool edge.
[0033] The columnar crystals of the support layer (metal bonding layer + nitride strengthening layer) are adjusted through the preparation process parameters (nitrogen content gradually increases) to obtain a micron-level columnar crystal structure perpendicular to the substrate, which can be used as a pure heat conduction channel to quickly dissipate the heat at the junction of the film layer and the substrate, delay the plastic deformation of the tool edge, and improve the cutting life of the tool;
[0034] The transition layer nano multilayer structure can produce a significant "superlattice" strengthening effect by adjusting the rotating frame speed (1r / min-2r / min) and alternately depositing a single layer of nano coating with a thickness of more than 50nm-25nm, which can increase the hardness of the coating while also inhibiting the interlayer expansion of cracks;
[0035] The functional layer columnar crystals have good anisotropic properties due to their coarseness, which reduces the grain boundaries. They are equivalent to two adjacent single crystals in microscopic terms. It is difficult for cracks to cross the strongly anisotropic interface, which makes the coating resistant to creep, fatigue and thermal shock. At the same time, submicron and nano-scale ceramic reinforcement phases are formed between the columnar crystals and distributed along the grain boundaries, which simultaneously improves the hardness and wear resistance of the coating and the reliability of damage protection of tools used in extreme environments.
[0036] 3. In the preparation method of the novel low-cost composite structure high-entropy ceramic coating provided by the present invention, two target materials, TiZrAlCrSiN and TiZrAlCrSiMN, are used for simultaneous deposition. The performance of the high-entropy ceramic coating can be further enhanced by structural regulation. In the co-deposition mode of the two target materials, the target material cost can be greatly saved, the processing cycle can be shortened, and the deposition efficiency can be improved, which is conducive to engineering promotion. It is a low-cost high-entropy ceramic coating preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic diagram of the structure of the novel low-cost composite high-entropy ceramic coating according to the present invention;
[0038] Figure 2a This is a surface thickness diagram of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 1 of the present invention;
[0039] Figure 2b This is a surface morphology of a novel low-cost composite structure high-entropy ceramic coating prepared in Example 1 of the present invention;
[0040] Figure 2c This is a friction coefficient curve of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 1 of the present invention;
[0041] Figure 3a This is a surface thickness diagram of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 2 of the present invention;
[0042] Figure 3b This is a surface morphology of a novel low-cost composite structure high-entropy ceramic coating prepared in Example 2 of the present invention;
[0043] Figure 3c This is a friction coefficient curve of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 2 of the present invention;
[0044] Figure 4a This is a surface thickness diagram of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 3 of the present invention;
[0045] Figure 4bThis is a surface morphology of a novel low-cost composite structure high-entropy ceramic coating prepared in Example 3 of the present invention;
[0046] Figure 4c This is a friction coefficient curve of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 3 of the present invention;
[0047] Figure 5a This is a surface thickness diagram of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 4 of the present invention;
[0048] Figure 5b This is a surface morphology of a novel low-cost composite structure high-entropy ceramic coating prepared in Example 4 of the present invention;
[0049] Figure 5c This is a friction coefficient curve of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 4 of the present invention;
[0050] Figure 6a This is a surface thickness diagram of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 5 of the present invention;
[0051] Figure 6b This is a surface morphology of a novel low-cost composite structure high-entropy ceramic coating prepared in Example 5 of the present invention;
[0052] Figure 6c This is a friction coefficient curve of the novel low-cost composite structure high-entropy ceramic coating prepared in Example 5 of the present invention;
[0053] Figure 7 This is a comparison chart of the film-substrate bonding strength of the novel low-cost composite structure high-entropy ceramic coating prepared in Examples 1 to 5 of the present invention;
[0054] Figure 8 This is a comparison chart of thermal conductivities of the novel low-cost composite structure high-entropy ceramic coatings prepared in Examples 1 to 5 described in the present invention;
[0055] Fig. 9 This is a comparison chart of the Vickers hardness of the novel low-cost composite structure high-entropy ceramic coating prepared in Examples 1 to 5 described in the present invention. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0057] like Figure 1As shown, the present invention provides a novel low-cost composite structure high-entropy ceramic coating, comprising: a support layer 110, a transition layer 120 and a functional layer 130 coated on a substrate 100; wherein the support layer 110 further comprises a TiZrAlCrSi layer (adhesive layer 111) and a TiZrAlCrSiN layer (strengthening layer 112) deposited in sequence, the transition layer 120 comprises a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer comprises a TiZrAlCrSiMN layer;
[0058] The chemical composition and mass percentage of the TiZrAlCrSi layer are as follows: Ti: 40% to 55%, Zr: 25% to 30%, Al: 10% to 25%, Cr: 5%, Si: 5%;
[0059] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 15%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0060] The chemical composition and mass percentage of the TiZrAlCrSiMN layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 12.5%, Cr: 2.5% to 5%, Si: 1.5% to 2.5%, M: 1% to 2.5%, N: 50%; M represents one or more of Hf, Y, and Nb.
[0061] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0062] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0063] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0064] Step 3: After the injection is completed, the support layer 110 is deposited: the rotation speed is 2-4r / min, the flow rate of nitrogen and argon is adjusted (the nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and the argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 2.4-3.6Pa, and the TiZrAlCrSi target arc source power source is turned on to deposit the TiZrAlCrSi layer (adhesive layer 111) and the TiZrAlCrSiN layer (strengthening layer 112) in sequence. The target material is Ti p Zr q Al r Cr s Si t , where p, q, r, s, t satisfy 0.40≤p≤0.55, 0.25≤q≤0.30, 0.10≤r≤0.25, s=0.05, t=0.05, p+q+r+s+t=1; set the current to 90~120A, bias voltage to -50~-350V, deposition time to 10~30min, thickness to 0.5~1.5um;
[0065] Step 4, deposition of transition layer 120: the rotation speed is 1-2r / min, the vacuum is maintained at 2.4-3.6Pa, the TiZrAlCrSiM target arc source power supply is turned on, and the TiZrAlCrSiN layer and the TiZrAlCrSiMN layer with a nano multilayer structure are periodically and alternately deposited, and then the TiZrAlCrSi target arc source power supply and the TiZrAlCrSiM target arc source power supply are turned off. The target material is Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.05≤d≤0.10, 0.03≤e≤0.05, 0.02≤f≤0.05, a+b+c+d+e+f=1, current is set to 90~120A, bias voltage is -50~-350V, deposition time is 90~150min, and thickness is 4.5~7.5um;
[0066] Step 5: Deposit the functional layer 130: Keep other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer, the target material is Ti a Zr b Al c Cr d Si e M f, formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.05≤d≤0.10, 0.03≤e≤0.05, 0.02≤f≤0.05, a+b+c+d+e+f=1, current is set to 90~120A, bias voltage is -50~-350V, deposition time is 10~30min, and thickness is 0.5~1.5um;
[0067] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation;
[0068] In steps 3 to 5, 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.05, 0≤|te|≤0.10.
[0069] The present invention will be further described below in conjunction with specific embodiments.
[0070] Example 1
[0071] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0072] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0073] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0074] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05, set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0075] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.0 3 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 120min;
[0076] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 30min;
[0077] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0078] The novel low-cost composite structure high-entropy ceramic coating prepared in this embodiment includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0079] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0080] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0081] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Y: 1%, N: 50%.
[0082] Example 2
[0083] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0084] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0085] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0086] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0087] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.0 3 Y 0.02, set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 150min;
[0088] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0089] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0090] The novel low-cost composite structure high-entropy ceramic coating prepared in this embodiment includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0091] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0092] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0093] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Y: 1%, N: 50%.
[0094] Example 3
[0095] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0096] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0097] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0098] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.50 Zr 0.30 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 30min;
[0099] Step 4: Deposit transition layer: Set the turret to the revolution mode (rotate perpendicular to the target surface) at a speed of 1-2 r / min, maintain the vacuum at 3.0 Pa, turn on the TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off the TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Nb 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 100min;
[0100] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Nb 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 20min;
[0101] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0102] The novel low-cost composite structure high-entropy ceramic coating prepared in this embodiment includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0103] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 50%, Zr: 30%, Al: 10%, Cr: 5%, Si: 5%;
[0104] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 25%, Zr: 15%, Al: 5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0105] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Nb: 1%, N: 50%.
[0106] Example 4
[0107] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0108] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0109] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0110] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 15min;
[0111] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Hf 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 120min;
[0112] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Hf 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 15min;
[0113] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0114] The novel low-cost composite structure high-entropy ceramic coating prepared in this embodiment includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0115] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0116] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0117] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Hf: 1%, N: 50%.
[0118] Example 5
[0119] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0120] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0121] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0122] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.6Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0123] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.20 Al 0.20 Cr 0.10 Si 0.0 5 Y 0.03 Hf 0.02, set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 90min;
[0124] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.20 Al 0.20 Cr 0.10 Si 0.05 Y 0.03 Hf 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 30min;
[0125] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0126] The novel low-cost composite structure high-entropy ceramic coating prepared in this embodiment includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0127] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 55%, Zr: 25%, Al: 10%, Cr: 5%, Si: 5%;
[0128] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 27.5%, Zr: 12.5%, Al: 5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0129] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 10%, Al: 10%, Cr: 5%, Si: 2.5%, Y: 1.5%, Hf: 1%, N: 50%.
[0130] Comparative Example 1
[0131] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0132] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0133] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10-2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0134] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 5min;
[0135] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.0 3 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 120min;
[0136] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 30min;
[0137] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0138] The novel low-cost composite structure high-entropy ceramic coating prepared in this comparative example includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0139] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0140] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0141] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Y: 1%, N: 50%.
[0142] Comparative Example 2
[0143] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0144] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0145] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0146] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0147] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.0 3 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 120min;
[0148] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 40min;
[0149] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0150] The novel low-cost composite structure high-entropy ceramic coating prepared in this comparative example includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0151] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0152] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0153] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Y: 1%, N: 50%.
[0154] Comparative Example 3
[0155] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0156] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0157] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0158] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 10min;
[0159] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.0 3 Y 0.02, set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 60min;
[0160] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 30min;
[0161] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0162] The novel low-cost composite structure high-entropy ceramic coating prepared in this comparative example includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0163] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0164] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0165] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Y: 1%, N: 50%.
[0166] Comparative Example 4
[0167] The present invention provides a novel method for preparing a low-cost composite structure high-entropy ceramic coating, comprising the following steps:
[0168] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0169] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0170] Step 3: After the injection is completed, the support layer is deposited: the rotation speed is 2-4r / min, the nitrogen and argon flow values are adjusted (nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and argon partial pressure decreases from 2.4-3.6Pa to 0), the vacuum is maintained at 3.0Pa, and the TiZrAlCrSi target arc source power supply is turned on to deposit TiZrAlCrSi layer and TiZrAlCrSiN layer in sequence. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 20min;
[0171] Step 4: Deposit transition layer: rotate at 1-2 r / min, keep vacuum at 3.0 Pa, turn on TiZrAlCrSiM target arc source power supply, periodically and alternately deposit TiZrAlCrSiN layer and TiZrAlCrSiMN layer with nano multilayer structure, then turn off TiZrAlCrSi target arc source power supply and TiZrAlCrSiM target arc source power supply. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.0 3 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 120min;
[0172] Step 5: Deposition of functional layer: Keeping other preparation parameters unchanged, turn on the TiZrAlCrSiM target arc source power source to deposit the TiZrAlCrSiMN layer. The target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.05 Si 0.03 Y 0.02 , set the current to 90~120A, bias voltage to -50~-350V, and deposition time to 5min;
[0173] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0174] The novel low-cost composite structure high-entropy ceramic coating prepared in this comparative example includes a support layer, a transition layer and a functional layer deposited in sequence; wherein the support layer includes a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited in sequence, the transition layer includes a periodically alternately deposited TiZrAlCrSiN layer and a TiZrAlCrSiMN layer, and the functional layer includes a TiZrAlCrSiMN layer;
[0175] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%;
[0176] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%;
[0177] The chemical composition of the TiZrAlCrSiMN layer and its mass percentage are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 1.5%, Y: 1%, N: 50%.
[0178] Test Case
[0179] In the present invention, the following performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4:
[0180] Nanohardness test: Micro Materials Vantage nanomechanical system, based on the technical specification of JB / T12721-2016 "Solid Material In-situ Nanoindentation Scratch Tester", uses the commonly used diamond tip, 10 points are tested on each sample, and then the average value is taken. The indentation depth is 1 / 10 of the coating thickness, and the surface hardness of the sample is tested at room temperature and 500°C.
[0181] Vickers hardness test: HXD-1000 Vickers microhardness tester, based on GB / T 4340.1-2009 "Metallic materials Vickers hardness test Part 1: Test method", at the 200gf force position, the loading and holding time is set to 10s, and 10 points are measured for each sample.
[0182] Membrane-substrate bonding strength test: RST3 macro scratch tester, scratch length 3 mm, scratch displacement speed 3 mm / min, starting load 1 N, and ending load 200 N.
[0183] Thermal conductivity test: LW-9389 interface material thermal resistance and thermal conductivity coefficient tester. This test method is based on an idealized steady-state heat conduction between two parallel isothermal panels separated by a sample of uniform thickness. After reaching the steady state, the temperature gradient generated by the temperature difference between the two isothermal surfaces in contact with the sample acts on the sample, causing heat flow through the sample. The direction of the heat flow should be along the normal of the sample contact interface. The size of the heat flow should be evenly distributed on the test surface, and there should be no lateral heat leakage. The thermal conductivity of the sample is calculated.
[0184] Friction coefficient: This experiment uses the HT-500 ball-disc rotating friction and wear tester to test the curve of the friction coefficient of the coating at the initial stage of wear as the friction time changes. The test is carried out at room temperature, the friction pair is direct 6mm SiC, the friction time is 30min, the friction radius is 4mm, the load is 200g, and the rotation speed is 200r / min.
[0185] As shown in Table 1 and Table 2, the test results are as follows:
[0186] Table 1 Test results
[0187]
[0188]
[0189] Table 2 Test results
[0190]
[0191] Figure 2a , 3a , 4a, 5a, and 6a are cross-sectional morphology diagrams of the examples of the present invention. It can be seen that the prepared coating has an obvious layer-in-layer structure, and the interface between the layers is clear and flat, no cracks are generated, and it is relatively dense, and the bonding strength with the substrate is more than 55N ( Figure 7 ) can ensure that there will be no premature cracking during cutting.
[0192] Figure 2b , 3b , 4b, 5b, and 6b are cross-sectional morphology diagrams of examples of the present invention. It can be seen that the surface quality of the prepared coating is good, and there are some white bright particles. This is because during the coating deposition process, the arc temperature is very high, causing the surface of the target material to melt, and the unionized neutral atoms will be ejected in the form of droplets and deposited on the surface of the film to form droplet contamination. It can be seen from the examples that when the target material composition is similar, reducing the coating time is conducive to improving the surface quality of the prepared coating.
[0193] Figure 2c , 3c, 4c, 5c, and 6c are the friction coefficient curves of the examples of the present invention. It can be seen that the wear process of the coating must go through the running-in wear stage before entering the stable wear stage. In the running-in stage, the friction coefficient of the coating is low. As the wear progresses, the friction coefficient increases, which is closely related to the droplet contamination defects on the coating surface. After 30 minutes of wear time, the average friction coefficient is 0.5-0.6. The wear process is relatively stable and the wear resistance is excellent.
[0194] Figure 8 The thermal conductivity test results of the embodiments of the present invention are listed. Thermal conductivity refers to the thermal conductivity of a material, which indicates the change in the temperature gradient of the material when the heat per unit area per unit time passes through a unit thickness. The greater the thermal conductivity, the better the thermal conductivity of the material. After testing, the thermal conductivity of the coating prepared in the embodiment can be up to 19.098W / (m·K), which has good thermal conductivity and can provide a thermal barrier for the tool substrate, allowing the generated heat to be transferred to the chips, thereby reducing the thermal load of the tool edge and preventing or delaying the plastic deformation of the tool edge.
[0195] Fig. 9 The Vickers hardness test results of the embodiments of the present invention are listed as follows. It can be seen that the Vickers hardness is greater than 3500HV, the maximum Vickers hardness is 3950HV, and the room temperature hardness is increased by 20%-50% compared with traditional TiN, CrN, AlTiN, AlCrSiN and other coatings.
[0196] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a novel low-cost composite structure high-entropy ceramic coating, characterized in that: The steps include: Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, heat the substrate, and perform ion implantation; Step 2: Adjust the flow rate of nitrogen and argon, maintain the vacuum state, and turn on the TiZrAlCrSi target arc power supply to deposit the support layer; wherein the nitrogen partial pressure increases from 0Pa to 2.4-3.6Pa, and the argon partial pressure decreases from 2.4-3.6Pa to 0; Step 3: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiM target arc power supply to deposit the transition layer, and then turn off the TiZrAlCrSi target arc source power supply and the TiZrAlCrSiM target arc source power supply; Step 4: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiM target arc power supply to deposit the functional layer, then turn off the TiZrAlCrSiM target arc power supply and cool it to obtain the novel low-cost composite structure high-entropy ceramic coating.
2. The method for preparing the novel low-cost composite structure high-entropy ceramic coating according to claim 1, characterized in that: In the step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface; and Evacuate to 5×10-2Pa, heat to 400-500℃ and keep warm for 60min.
3. The method for preparing the novel low-cost composite structure high-entropy ceramic coating according to claim 1, characterized in that: In the step 1, the ion implantation conditions include: selecting Ti as the cathode, an extraction voltage of 10-15 kV, a trigger frequency of 0-15 Hz, controlling the target current to 80-12 mA, and an implantation time of 30 min.
4. The method for preparing a novel low-cost composite structure high-entropy ceramic coating according to claim 2 or 3, characterized in that: In the step 2, the coating speed is set to 2-4 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
5. The method for preparing the novel low-cost composite structure high-entropy ceramic coating according to claim 4, characterized in that: In the step three, the coating speed is set to 1-2 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
6. The method for preparing the novel low-cost composite structure high-entropy ceramic coating according to claim 4, characterized in that: In the step 4, the coating speed is set to 1-2 r / min, and the vacuum state is maintained at 2.4-3.6 Pa.
7. The method for preparing a novel low-cost composite structure high-entropy ceramic coating according to any one of claims 1-3, 5, and 6, characterized in that: Set the TiZrAlCrSiM target to Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.05≤d≤0.10, 0.03≤e≤0.05, 0.02≤f≤0.05, a+b+c+d+e+f=1, current is 90~120A, bias voltage is -50~-350V, and deposition time is 10~30min; Set the TiZrAlCrSi target to Ti p Zr q Al r Cr s Si t , where p, q, r, s, t satisfy 0.40≤p≤0.55, 0.25≤q≤0.30, 0.10≤r≤0.25, s=0.05, t=0.05, p+q+r+s+t=1, current is 90~120A, bias voltage is -50~-350V, deposition time is 10~30min; Among them, 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.05, 0≤|te|≤0.
10.
8. A new type of low-cost composite structure high entropy ceramic coating, characterized in that: The novel low-cost composite structure high-entropy ceramic coating is prepared by the preparation method according to any one of claims 1 to 7, wherein the novel low-cost composite structure high-entropy ceramic coating comprises a support layer, a transition layer and a functional layer deposited in sequence; Wherein, the support layer comprises a TiZrAlCrSi layer and a TiZrAlCrSiN layer deposited sequentially, the transition layer comprises a TiZrAlCrSiN layer and a TiZrAlCrSiMN layer deposited periodically and alternately, and the functional layer comprises a TiZrAlCrSiMN layer; The chemical composition and mass percentage of the TiZrAlCrSi layer are as follows: Ti: 40% to 55%, Zr: 25% to 30%, Al: 10% to 25%, Cr: 5%, Si: 5%; The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 15%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%; The chemical composition and mass percentage of the TiZrAlCrSiMN layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 12.5%, Cr: 2.5% to 5%, Si: 1.5% to 2.5%, M: 1% to 2.5%, N: 50%; M represents one or more of Hf, Y, and Nb.
9. The novel low-cost composite structure high-entropy ceramic coating according to claim 8, characterized in that: The thickness of the support layer is 0.5-1.5 um, the thickness of the transition layer is 4.5-7.5 um, and the thickness of the functional layer is 0.5-1.5 um.
10. Application of a new type of low-cost composite structure high entropy ceramic coating in dry cutting tools, characterized in that: Use the novel low-cost composite structure high-entropy ceramic coating as described in claim 8.
Citation Information
Cited By
Selective ion drag interface enhanced metal ceramic cutter and preparation method
CN121802358A
